In Vitro Study of The Activity of Yellow Rope (Anamirta cocculus) Extract As An Antibacterial - Darmayanti Tumpu; A.M. Muslihin; Lukman Hardia (Jurnal Penelitian Pendidikan IPA, 2025)
A. cocculus is an endemic plant to Papua, which is often used as medicine. This study aims to determine the antibacterial activity of the ethanol extract of A. cocculus stems against P. acne, S. aureus, and E. coli bacteria. This research also has the potential to be used as a contextual learning resource in biology classes, especially on the topic of antibacterial and secondary metabolite testing, using experimental methods. The antibacterial activity test was carried out using the disk diffusion method, which was performed in 3 concentrations, namely 5%, 10%, and 15%. The positive control used 2 μg of clindamycin antibiotic and 30 μg of chloramphenicol antibiotic; the negative control used Aqua Pro injection. Measurement of the diameter of the inhibition zone shows that A. cocculus extract can inhibit bacterial growth, concentration 5% (P. acnes = 9.18mm/medium; S. aureus = 9.17/medium, and E. coli = 3.91/weak), concentration 10% (P. acnes = 11.86mm/strong; S. aureus = 11.88/strong, and E. coli = 5.17mm/medium), and concentration 15% (P. acnes = 11.56/strong; S. aureus = 12.9/strong, and E. coli = 5.86/medium).